Delay-dependent consensus condition for a class of fractional-order linear multi-agent systems with input time-delay. Issue 4 (12th March 2019) - Shi, Min; Yu, Yajuan; Xu, Qi
Abstract : The consensus problem of a class of fractional-order linear multi-agent systems with distributed control containing input time-delay is investigated. By adopting the frequency domain analysis and generalised Nyquist criterion for the fractional-order time-delay systems, the delay-dependent consensus condition is obtained. Then, we are interested in finding the maximum time-delay tolerance and give an exact formula for calculating the maximum time-delay to maintain the system is consensusable. As illustrated by the numerical examples, the proposed theoretical results work effectively and accurately.